Upaya Meningkatkan Kemampuan Membaca Lancar dengan Menerapkan Model Pembelajaran Cooperative Learning Tipe Make a Match Siswa Kelas III Semester 2 SD Negeri 64/IV Kota Baru Jambi - Sawiyah Sawiyah (Universitas Batanghari Jambi, 2019)
This research is backed up that the learning outcomes of elementary School 64/IV Jambi city is still low 58.69 with its submission to only 17.39%, which is only 4 people from 23 class III students elementary School 64/IV Jambi City. This is due to the lack of active participation and student involvement during the learning process. In addition before being addressed this PTK teacher has not used the Make A Match type method, just more using the lecture method. Teachers need to implement learning methods that can encourage student involvement in learning. The Make A Match type method is one of the methods that can fulfill these expectations. The purpose of this research is to know whether the Make A Match type method can increase learning activity and student learning outcomes. This research is a class action research (PTK) with the subject of research is a class III students of even semester (2) Elementary School 64/IV Kota Jambi. The methods of data collection that are tested in this study are the methods of testing and observation. Collected Data is analyzed with qualitative descriptive analysis. The results showed that there was an increase in student activity and learning outcomes after receiving learning with the Make A Match type method. The results of increased learning outcomes and student activity will experience an increase in the reading smoothly for students of class III D SD 64/IV of Jambi City. The increase in the I cycle of 64.58 Learning management while the II cycle has increased to be 89.58% very good category. If the management is very good certainly affects the outcome of learning and activity of students that is cycle I activity students 70.58 enough categories while cycle II multiply the increase to 92.83 category very well. Further to the results of learning in the I 65.22 cycle category is enough while the II cycle is experiencing a peningktan to 79.80 good categories. It can be concluded that using a problem-based learning method can improve learning activities and student learning outcomes.